Recent advances in applications of green nanocomposites in enhanced oil recovery: a comprehensive review of different characterization methods and effective parameters - Meysam Hemmati; Yaser Ahmadi (Journal of Petroleum Exploration and Production Technology)
Abstract Researchers are aware of the many advantages of studying green nanocomposites, which are made from safe industrial materials or taken from plants. Because of these peculiar characteristics, petroleum engineers find green NCs to be highly attractive as an alternative addition for EOR techniques. These substances are non-toxic, safe for humans, and harmless to other living things. Common investigations like XRD, FTIR spectroscopy, SEM, and Zeta Potential tests are used to detect and evaluate nanoparticles. Additionally, they are economical and environmentally friendly due to the low doses of NCs needed for EOR techniques. The bold features in EOR by NCs are their micro sizes that enabled them to travel easier within pore throats, as well as their high reactivity to change parameters impact on mobilization of trapped oil in tight pores. A suspension of nanoparticles with low concentration is sufficient to modify fluid flow parameters in reservoir porous media. Modifying mainly includes wettability alteration, interfacial tension reduction, changing disjoining pressure, and emulsification, which all help more fluid mobility and improve oil recovery. These materials have the tendency to displace water and improve the flow of oils toward production wells. In some cases, the contact angle dropped down from 161 to 28° or from 151 to 14°, which led to the creation of strong hydrophilic (water-wet) systems. The interfacial tension is also greatly diminished according to the modifying character of NCs, so that causes a reduction in IFT of more than 33.8 mN/m. By 30–50% OOIP, the EOR techniques can produce larger volumes of oil, while nanotechnology is capable of more oil recovery up to 50–60% OOIP. This review’s primary focus is on introducing green NCs that most of them synthesized after 2020 and are applicable in petroleum production.